2017
DOI: 10.1007/s00024-017-1728-2
|View full text |Cite
|
Sign up to set email alerts
|

Voids and Rock Friction at Subseismic Slip Velocity

Abstract: Abstract-We found that the amplitudes of transmitted waves across the sliding surfaces are inversely correlated to high slip rate friction, especially when the interfaces slide fast ([ 10 -3 m/s). During the rock-rock friction experiments of metagabbro and diorite at sub-seismic slip rate (* 10 -3 m/s), friction does not reach steady state but fluctuates within certain range. The amplitudes of compressional waves transmitted across the slipping interfaces decrease when sliding friction becomes high and it incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Fukuyama et al. (2018) studied amplitude variation during high‐velocity friction experiments. Moreover, Shreedharan et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fukuyama et al. (2018) studied amplitude variation during high‐velocity friction experiments. Moreover, Shreedharan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Scuderi et al (2016) explored the complete spectrum of failure modes, from slow to fast earthquakes, showing that not only co-seismic changes but also precursory variations of P-wave velocity occur for each mode of failure. Fukuyama et al (2018) studied amplitude variation during high-velocity friction experiments. Moreover, Shreedharan et al (2021) showed clear precursory P-wave amplitude variations occurring with the instability nucleation phase and precursory P-wave velocity variations distorted by the presence of the surrounding bulk material.…”
mentioning
confidence: 99%
“…Figure 1a shows a schematic diagram of the apparatus. A pair of rock specimens made of Indian metagabbro (see Fukuyama et al 2016 for its mineral composition) was used. The lower specimen moved with the shaking table and the upper specimen was fixed to the outer base of the shaking table by a reaction force bar.…”
Section: Introductionmentioning
confidence: 99%